Efficacy of Senna occidentalis Leaf Extracts in the Treatment of Bacterial Gastroenteritis - Esther GEORGE NYADZUA; Onyango EVANDER OCHIENG; Lunani KEITH WAKASIAKA; Uhuru FAITH BERYL; Kariuki JOSHUA; Rop MOSES KIPLIMO; Titus SUGE; Michael WALEKHWA (African Journal of Pharmacy and Alternative Medicine, 2026)
Bacterial gastroenteritis remains a significant global health challenge due to the rising issue of antibiotic resistance and the high cost of conventional drugs, especially in low-resource settings. Addressing this gap, this study evaluated the efficacy of Senna occidentalis leaf extracts in treating bacterial gastroenteritis through an in vitro laboratory-based experimental design. Before the commencement of the study, an Ethical clearance certificate and a permit to conduct the study were sought from Kabarak University Research Ethics Committee (KUREC) and National Commission for Science, Technology and Innovation (NACOSTI), respectively. Mature S. occidentalis leaves were collected from Kilifi County, authenticated, and extracted using methanol, petroleum ether, and distilled water. Phytochemical screening was carried out using standard qualitative methods. Antibacterial activity against Salmonella paratyphi was assessed using the disk diffusion method and Minimum Inhibitory Concentration (MIC) tests, with ciprofloxacin as the positive control and DMSO as the negative control. Methanol extraction produced the highest yield (29.15%), followed by aqueous (13.78%) and petroleum ether (4.32%). Phytochemical analysis revealed high levels of alkaloids, tannins, coumarins, flavonoids, anthraquinones, and cardiac glycosides, with saponins present in low amounts. All extracts showed measurable antibacterial activity, with petroleum ether extracts demonstrating relatively stronger inhibition at lower concentrations and aqueous extracts performing better at higher concentrations. Ciprofloxacin produced significantly larger inhibition zones than all extracts. Data were analyzed using descriptive and non-parametric statistical tests (Kruskal-Wallis and Spearman correlation) in SPSS Version 27 at 95% confidence. The study successfully evaluated the efficacy of Senna occidentalis leaf extracts against Salmonella paratyphi, confirming its antibacterial potential. However, the modest inhibition zones compared to ciprofloxacin underscore the need for bioassay-guided fractionation, in vivo testing, and toxicity evaluation to isolate and enhance active constituents.